Intestinal Rehabilitation Programs in the Management of Pediatric Intestinal Failure and Short Bowel Syndrome. Issue 5 (November 2017) - Merritt, Russell J.; Cohran, Valeria; Raphael, Bram P.; Sentongo, Timothy; Volpert, Diana; Warner, Brad W.; Goday, Praveen S.
Abstract : ABSTRACT: Intestinal failure is a rare, debilitating condition that presents both acute and chronic medical management challenges. The condition is incompatible with life in the absence of the safe application of specialized and individualized medical therapy that includes surgery, medical equipment, nutritional products, and standard nursing care. Intestinal rehabilitation programs are best suited to provide such complex care with the goal of achieving enteral autonomy and oral feeding with or without intestinal transplantation. These programs almost all include pediatric surgeons, pediatric gastroenterologists, specialized nurses, and dietitians; many also include a variety of other medical and allied medical specialists. Intestinal rehabilitation programs provide integrated interdisciplinary care, more discussion of patient management by involved specialists, continuity of care through various treatment interventions, close follow-up of outpatients, improved patient and family education, earlier treatment of complications, and learning from the accumulated patient databases. Quality assurance and research collaboration among centers are also goals of many of these programs. The combined and coordinated talents and skills of multiple types of health care practitioners have the potential to ameliorate the impact of intestinal failure and improve health outcomes and quality of life.